ANALISA SENSITIVITAS RESPON KONSUMEN TERHADAP PERLUASAN LINI (LINE EXTENTION) PADA MIE CUP MEREK POP MIE DI PEKANBARU - Rendy Yonelananda Putra; Aida Nursanti; Tengku Firly Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Competitive conditions are increasingly growing rapidly fueled traders and manufacturers are competing to win the competition by trying to grab a large market share. To cope with the competition, companies take a variety of ways and strategies to deliver their products fast, precise, accurate, cost-effective and satisfying to consumers, the products are diverse with a wide variety of brands has started being introduced by various companies. PT. Indofood Sukses Makmur has issued many new products and implement the line extension strategy by releasing products that are different from the products that have been issued previously. As from Pop Mie Goreng Pedas to Pop Mie Baso. This study aims to determine how much the level of sensitivity and direction household consumer response to the extension line (line extension) on the Cup Noodle brand Pop Mie in Pekanbaru Pop 100 respondents housewife. The sampling technique used in this research is area sampling. This research is a descriptive analysis,where it can describe about phenomenon of company PT. Indofood successful prosperous conducting line extension. The results showed that consumers had a response that is sensitive to the line extension of Pop Mie Goreng Pedas to Pop Mie Baso is equal to 1.26. While the direction is a positive response, which means the consumer or the respondent to behave in accordance with the desired company.Keywords : Line Extention, Level Sensitivity, and Direction Response